Colour Perception on Facial Expression towards Emotion - Ching Yee Yong; Rubita Sudirman; Kim Mey Chew (Universitas Ahmad Dahlan, 2012)
This study is to investigate human perceptions on pairing of facial expressions of emotion with colours. A group of 27 subjects consisting mainly of younger and Malaysian had participated in this study. For each of the seven faces, which express the basic emotions neutral, happiness, surprise, anger, disgust, fear and sadness, a single colour is chosen from the eight basic colours for the “match” of best visual look to the face accordingly. The different emotions appear well characterized by a single colour. The approaches used in this experiment for analysis are psychology disciplines and colours engineering. These seven emotions are being matched by the subjects with their perceptions and feeling. Then, 12 male and 12 female data are randomly chosen from among the previous data to make a colour perception comparison between genders. The successes or failures in running of this test depend on the possibility of subjects to propose their every single colour for each expression. The result will translate into number and percentage as a guide for colours designers and psychology field.